Educação em valores: solução para a violência e indisciplina na escola? - Zechi, Juliana Aparecida Matias [UNESP] (2014)
This research is part of the research line Formative processes, Differences and Values of the Post-Graduate Programme in Education of the Faculty of Science and Technology/Universidade Estadual Paulista. Behavior problems considered by teachers as violence, indiscipline and lack of respect have been pointed, indistinctly, as one of the biggest obstacles to pedagogical practice. At the same time, cause a search for strategies that can improve the quality of interpersonal relationships in schools and the teaching-learning process. This research, which is a descriptive study with a qualitative approach, aims to investigate the relationships that the public school and its agents make on Education in Values and the confronting of violence and the school indiscipline and what training they have received to act in this area. To this end, was carried out a theoretical review of books and articles in the area to survey the relationships made there on Education in Values, violence and school indiscipline; below, were selected projects of Education in Values aimed at confronting of violence and indiscipline conducted in Brazilian public schools. The survey of projects was done from a database available from the research Successful projects of moral education: in search of Brazilian experiences, started in 2008, who applied a questionnaire to directors, pedagogical coordinators and teachers in public schools from various regions of Brazil. A total of 193 experiments were selected...